The Effect of Lecture Recordings on Lecture Attendance: Law Academics’ Misconceptions and Law Students’ Reality - Do, Christina (Australasian Law Teachers Association, 2017)
An issue experienced globally in the higher education sector is the reported decline in student attendance at lectures over the course of a study period. In 2017, a small-scale pilot project was conducted at the Curtin Law School (‘CLS’) to explore what, if any effect, the availability of lecture recordings has on student attendance at lectures in the discipline of Law. The project involved asking CLS law academics and students, to complete a questionnaire about their opinions on the use of face-to-face lectures and lecture recordings, respectively. By researching the perspectives of law academics and law students, misalignments were identified between law academics’ perceptions of why lecture attendance by students is declining, and students’ actual learning needs and preferences. This paper outlines and critically analyses the data collected from the project and highlights the key misalignments identified — particularly a misconception by law academics that the availability of lecture recordings is the leading cause of declining rates of student attendance at lectures. This paper then offers learning and teaching strategies that law academics could use to encourage students to attend their lectures, and enhance students’ university learning and teaching experience.